Experimental Etching of Diamonds: Extrapolation to Impact Diamonds from the Popigai Crater (Russia) - Valeri Sonin; Egor Zhimulev; Aleksei Chepurov; Ivan Gryaznov; Anatoly Chepurov; Valentin Afanasiev; Nikolai Pokhilenko (Minerals, 2021)
Diamond etching in high-temperature ambient-pressure experiments has been performed aimed to assess possible postimpact effects on diamonds in impact craters, for the case of the Popigai crater in Yakutia (Russia). The experiments with different etchants, including various combinations of silicate melts, air, and inert gases, demonstrated the diversity of microstructures on {111} diamond faces: negative or positive trigons, as well as hexagonal, round, or irregularly shaped etch pits and striation. The surface features obtained after etching experiments with kimberlitic diamonds are similar to those observed on natural impact diamonds with some difference due to the origin of the latter as a result of a martensitic transformation of graphite in target rocks. Extrapolated to natural impact diamonds, the experimental results lead to several inferences: (1) Diamond crystals experienced natural oxidation and surface graphitization during the pressure decrease after the impact event, while the molten target rocks remained at high temperatures. (2) Natural etching of diamonds in silicate melts is possible in a large range of oxidation states controlled by O2 diffusion. (3) Impact diamonds near the surface of molten target rocks oxidized at the highest rates, whereas those within the melt were shielded from the oxidizing agents and remained unchanged.